The cardioprotective potential of selected species of mistletoe - Olas, Beata (Frontiers in Pharmacology, 2024)
Mistletoe is an evergreen woody shrub with stems measuring 30–100 cm. It has leathery, yellowish-green strap-shaped leaves, yellowish-green flowers, and bears typical berries. The most common species is Viscum album L., mainly present in Europe and Asia. It is commonly known as European mistletoe or simply, mistletoe. Scientific interest in mistletoe was awakened in the XX century. Mistletoe, especially V. album L., has historically been used in the treatment and prophylaxis of CVD, with its properties being confirmed in recent studies. This mini-review describes new aspects of the cardioprotective properties of various species of mistletoe, especially V. album L. The effect of oral and subcutaneous application of fresh V. album L. extracts on blood pressure has been studied in various models; while the data suggests that mistletoe may be a promising herbal extract with cardioprotective properties, the species has only been tested in vitro and in vivo, on animals. In addition, it is unclear whether the cardioprotective activity of mistletoe may be due to particular chemical components, as the chemical composition of mistletoe extracts can vary depending on inter alia the time of harvest, extraction method and plant part. Hence, this activity may instead result from synergistic interactions between various secondary metabolites. Therefore, further studies are needed to identify the mechanisms of action of mistletoe compounds on CVDs, and determine their interactions with other cardioprotective drugs, their metabolic mechanisms, pharamacokinetics and adverse effects. More research is also needed to determine the therapeutic doses of active ingredients for use in clinical trials; this would require an accurate understanding of the chemical composition of extracts from different species of mistletoe (not only V. album L.) and from various host trees.